Comparative analysis of the economic and social aspects that characterize the bolivarian countries: challenges and expectations - Caballero Tovio, Antonio (2018)
The purpose of this article is to analyze and compare the economic and social aspects of Bolivarian countries such as Bolivia, Colombia, Ecuador, Panama, Peru and Venezuela, to identify the similarities and differences framed throughout their history; In the same way, determine the challenges they are currently facing, and on the other hand, know the expectations that can be glimpsed in the medium and long term. For this purpose, an analytical descriptive study was used as a methodological framework, with a quantitative and qualitative approach, using and processing statistics on Gross Domestic Product GDP, Per Capita Income, GDP variation rate, Commercial Balance, Inflation, Rate of unemployment, and the IDH Human Development Index. This analysis allowed to know with critical thinking, the common features and differences between these countries, which in turn laid the foundations for a prospective vision in terms of the development of the economies of these countries. For this purpose, each of these economic variables was analyzed first, then the respective discussion was generated, and finally the findings and conclusions of the case.